Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Produk Eiger di Kota Surabaya - Fistia Shofil Ashfiyah; Iswati Iswati; Anis Fitriyasari; Arief Widijatmoko (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze brand image and product quality on purchasing decisions for Eiger products in the city of Surabaya. This research uses quantitative methods with questionnaire distribution techniques. Data was collected from respondents in the city of Surabaya, obtaining 75 respondents who purchased Eiger products. The results of the analysis carried out using SPSS in the t test show that brand image influences purchasing decisions with a t-value of 3,642 > ttable 1.9929 with a significance of 0.001 < 0.05 and product quality influences purchasing decisions with a t-count of 4,762 > ttable 1.9929 with a significance of 0.000 < 0.05. Meanwhile, the results of the f test show that brand image and product quality have a simultaneous influence on purchasing decisions with the calculated F value of 95.935 > F table 3.9739 with a significance of 0.000 < 0.05, which means that the brand image and product quality variables influence purchasing decisions. The findings of this research indicate that brand image and product quality are important factors that Eiger products need to consider in developing their marketing strategy.